MoS2-coated porous M-N-C monatomic catalyst and application thereof in lithium air battery

By coating the MoS2 layered structure in the cathode catalyst material of lithium air battery, the problems of unstable catalyst active site and low cycling performance are solved, the cycling performance and overvoltage stability of the battery are significantly improved, and excellent electrochemistry is achieved performance.

CN119481104AActive Publication Date: 2025-02-18HEFEI UNIV OF TECH

Patent Information

Application Number
CN202411625014.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing lithium air battery positive electrode catalyst materials have problems such as unstable active sites, low cycling performance, and high overvoltage, which limits its performance improvement.

Method used

Transition metal ions are chelated and anchored on a porous carbon support by chelating agent, mixed with nitrogen source precursor to form an M-N-C material, and then wrapped with layered MoS2 nanosheets through hydrothermal vulcanization and high-temperature calcination to prepare MoS2 coated porous M-N-C single atom catalyst.

Benefits of technology

The stability and electrochemical activity of the catalyst active site have been improved, and the circulation performance and overvoltage stability of lithium air batteries have been significantly improved. The first discharge specific capacity has reached 24896.46mAh/g, the overvoltage has been maintained at around 1.01V, and It can operate stably for 210 cycles at a current density of 500mA/g.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481104A_ABST
    Figure CN119481104A_ABST
Patent Text Reader

Abstract

The invention discloses a MoS2-coated porous M-N-C monatomic catalyst and an application thereof in a lithium air battery, the MoS2-coated porous M-N-C monatomic catalyst is prepared by the following steps: chelating transition metal ions through a chelating agent, anchoring the transition metal ions on a porous carbon carrier, mixing the transition metal ions with a nitrogen source precursor, and calcining to obtain a material which takes porous nitrogen-doped carbon as a carrier and loads a transition metal monatomic M, thereby obtaining the MoS2-coated porous M-N-C monatomic catalyst. And wrapping the layered MoS2 nanosheets through a hydrothermal vulcanization method and high-temperature calcination to obtain the target catalyst material. The obtained composite material has higher mass transfer efficiency, has higher oxygen reduction activity and stability in acidic and alkaline media, has lower overvoltage, high specific discharge capacity and excellent cycle performance when being used as a lithium air battery catalyst, and has better research prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery material preparation, and in particular to a MoS2-coated porous MNC single-atom catalyst and its application in lithium-air batteries. Background Art

[0002] Electric vehicles (EVs) can reduce greenhouse gas emissions and the use of petroleum-derived fuels, and have broad application prospects. However, the lithium-ion batteries commonly used in existing electric vehicles have the problem that the energy density cannot meet the demand. The performance of rechargeable lithium-air batteries far exceeds that of traditional lithium-ion batteries, and due to their ultra-high energy density, they are expected to become the "rising star" in the field of electric vehicles. However, lithium-air batteries also face many challenges, such as low cycle performance, high overvoltage, and instability of the electrolyte. In non-aqueous lithium-air batteries, the oxidation reaction (ORR, O2+2Li + +2e - →Li2O2) and redox reactions (OER, Li2O2→O2+2Li + +2e - ) plays an important role in the kinetics, but both are limited. In view of the above reasons, the development of an effective electrocatalyst is urgent for the development of lithium-air batteries.

[0003] Transition metal single-atom nitrogen-coordinated carbon-based (MNC, where M is one or two transition metals such as Fe, Co, Ni, etc.) materials have been widely prepared and show high catalytic activity and unique selectivity in electrocatalytic applications. Existing MNC materials are mostly prepared using MOFs-derived single-atom catalysts, and the catalysts obtained by this method generally have the problem of unstable active sites. Therefore, it is of great significance to study new processes for preparing MNC materials.

[0004] At the same time, designing a protective layer that can not only confine and protect the active center of the catalyst to maintain stability, avoid shedding and agglomeration, but also has excellent catalytic activity and can produce synergistic catalytic effects with MNC is also an effective way to solve the above problems. Molybdenum disulfide (MoS2) is a typical transition metal two-dimensional layered compound with a graphene-like layered structure. Its S-Mo-S "sandwich" structure determines that the bond energy between adjacent sulfur atomic layers is weak and the surface energy is low, while the binding energy of the S-Mo-S bond is very strong. The bond valence of the Mo and S atoms at the edge is unsaturated, with many dangling bonds, and is in a chemically unstable state, which makes the edge of the MoS2 crystal have a very high surface energy. Therefore, forming a MoS2 protective layer on the surface of the MNC material by a suitable method and forming a built-in heterostructure between the two is a feasible method to improve the stability of the active sites and electrochemical activity of the MNC material. Summary of the invention

[0005] In view of the shortcomings of existing lithium-air battery positive electrode catalyst materials, the purpose of the present invention is to provide a MNC@MoS2SACs composite material that can be prepared by a simple process method, has good conductivity and catalytic activity, and has stable catalytic active sites, and use it in lithium-air batteries to improve their performance.

[0006] In order to solve the technical problem, the present invention adopts the following technical solution:

[0007] The present invention first discloses a method for preparing a MoS2-coated porous MNC single-atom catalyst, which is characterized in that:

[0008] First, the transition metal ions are chelated and anchored on the porous carbon support by a chelating agent, and then mixed with a nitrogen source precursor and calcined to obtain a material with porous nitrogen-doped carbon as a support and loaded with transition metal single atoms M, which is denoted as MN-CSACs. During the calcination process, a new MN is formed that can improve the stability and activity of the catalyst. x At the same time, the chelated metal complex can fix the metal atoms to a certain position by decomposing the residue during the calcination and pyrolysis process, further improving its stability.

[0009] Then, through hydrothermal sulfurization and high-temperature calcination, the MNC SACs material was wrapped with layered MoS2 nanosheets to obtain MoS2-coated porous MNC single-atom catalysts, which were recorded as MNC@MoS2SACs.

[0010] The preparation method of MNC@MoS2SACs of the present invention specifically comprises the following steps:

[0011] Step 1, calcining 5-15 g of a carbon source precursor at 500-1000° C. for 1-10 hours to obtain a porous carbon nanosheet;

[0012] Step 2, 1-5g of chelating agent and 0.08-0.30g of transition metal salt are dissolved in deionized water and stirred evenly, then 0.05-0.2g of porous carbon nanosheets are added and ultrasonically dispersed evenly, and the mixture is allowed to stand for 12-24h, then centrifuged and dried, and the obtained powder is mixed and ground with a nitrogen source precursor in a mass ratio of 1:2.5-10, and then calcined at 500-1500°C for 1-10 hours to obtain MN-CSACs;

[0013] Step 3, 0.1-0.3g of molybdenum source, 0.2-0.4g of sulfur source and 0.1-0.2g of MNC SACs obtained in step 2 are evenly dispersed in 20mL of distilled water, transferred to a reactor, and reacted at 180-200°C for 15-36h; after the reaction, the obtained product is washed and dried, and then calcined at 500-1000°C for 2-4h to obtain the target product MNC@MoS2 SACs composite material.

[0014] Furthermore, the carbon source precursor is potassium phytate, anhydrous potassium citrate or plant fiber, preferably anhydrous potassium citrate (which has the characteristics of being porous and having a large specific surface area).

[0015] Furthermore, the chelating agent is glucose.

[0016] Furthermore, the transition metal is at least one of Fe, Co and Ni, and the transition metal salt is a nitrate, sulfate, acetate, oxalate or chloride of the transition metal, preferably a nitrate.

[0017] Furthermore, the nitrogen source precursor is dicyandiamide, melamine or urea, preferably melamine.

[0018] Furthermore: the sulfur source is thiourea, sulfur, thiol or thionine, preferably thiourea; the molybdenum source is ammonium molybdate tetrahydrate, molybdenum trioxide, calcium molybdate or molybdenum hexafluoride, preferably ammonium molybdate tetrahydrate.

[0019] Furthermore, the calcination in steps 1 to 3 is all carried out under the protection of inert gas.

[0020] The invention also discloses a MNC@MoS2 SACs composite material prepared by the preparation method, which can be used as a positive electrode catalyst material for a lithium-air battery.

[0021] Compared with the prior art, the present invention provides a novel method for preparing MoS2-coated porous MNC single-atom catalysts, and its beneficial effects are embodied in:

[0022] 1. The present invention first proposes a template-free integrated procedure for preparing non-polymeric high specific surface area oxygen-rich porous carbon nanosheets, which is simple and economical. In the preparation of porous carbon nanosheets, anhydrous potassium citrate is preferably used as a carbon source precursor, and the resulting nanosheets are interconnected to form a desert rose nanosheet structure, thereby increasing the diffusion rate of ions. The products obtained by using other carbon sources are in the form of flat carbon nanoparticles, and disordered aggregation occurs between the particles.

[0023] 2. The present invention uses the chelating agent glucose to chelate and anchor transition metal ions on an oxygen-rich porous carbon carrier with a high specific surface area, thereby effectively isolating the transition metal ions (primary protection) and stably binding them to the carbon carrier through interaction with O-containing groups. At the same time, excess glucose can bind to the support surface to physically isolate the transition metal complex (secondary protection), and glucose can further fix metal atoms by decomposing residues at a certain temperature. And when melamine is used as a nitrogen source precursor, glucose can also decompose with melamine at a higher temperature to form carbon and nitrogen species (such as C3N4) that can capture active metal single atoms and further combine with metal atoms to form M-Nx species. Multiple principles work together to more effectively prevent metal atoms from aggregating.

[0024] 3. The present invention utilizes the special structure of porous MoS2 to embed porous MoS2 in the shell of MNC. The confinement effect of the micropores and the anchoring effect of the functionalized surface can prevent the detachment and agglomeration of the active points of metal atoms during the preparation process, stabilize the uniform distribution of the active points on the carrier, and increase the density of the active sites.

[0025] 4. The composite material prepared by the present invention has higher mass transfer efficiency, higher oxygen reduction activity and stability in acidic and alkaline media, and has lower overvoltage, high discharge specific capacity and excellent cycle performance when used as a lithium-air battery catalyst. The results show that in a deep battery performance test under high-purity oxygen conditions (2.0-4.5V), the first discharge specific capacity at a current density of 100mA / g is 24896.46mAh / g, the overvoltage is maintained at about 1.01V, and it can stably operate for 210 cycles at a current density of 500mA / g, with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 X-ray diffraction patterns (XRD) of the catalyst materials prepared in Example 1 and Comparative Examples 1 and 2;

[0027] Figure 2 This is the EDS spectrum of the Co-NC@MoS2SACs composite material prepared in Example 1;

[0028] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of the Co-NC@MoS2SACs composite material prepared in Example 1, where (a) and (b) are TEM images at different magnifications, (c) is a HRTEM image, and (d) is a local enlarged image of (c).

[0029] Figure 4 The porous carbon nanosheet prepared in Example 1 ( Figure 4 (a)), Co-NC SACs ( Figure 4(b)), MoS2 prepared in Comparative Example 2 ( Figure 4 (c)) and Co-NC@MoS2SACs prepared in Example 1 ( Figure 4 Scanning electron microscope (SEM) image of (d)).

[0030] Figure 5 The first charge and discharge performance diagram of the lithium-air battery assembled with the catalyst materials prepared in Example 1 and Comparative Examples 1 and 2;

[0031] Figure 6 The cycle performance diagram of the lithium-air battery assembled with the catalyst materials prepared in Example 1 and Comparative Examples 1 and 2;

[0032] Figure 7 Overvoltage diagram of lithium-air batteries assembled with catalyst materials prepared in Example 1 and Comparative Examples 1 and 2;

[0033] Figure 8 These are ORR performance test diagrams of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2, wherein a to e represent the materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2, respectively. DETAILED DESCRIPTION

[0034] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0035] Example 1

[0036] Step 1: Place 5 g of anhydrous potassium citrate in a crucible, move it into a tube furnace, and calcine it at 800° C. for 1 h in argon protection to obtain porous carbon nanosheets.

[0037] Step 2: Dissolve 1.33 g of glucose and 0.0873 g of cobalt nitrate hexahydrate in 5 mL of distilled water, stir evenly, add 60 mg of porous carbon nanosheets, ultrasonicate for 30 min, let stand for 24 h, then centrifuge, wash with water several times, and vacuum dry. The resulting powder is then mixed with melamine in a mass ratio of 1:5 and ground, and calcined at 800 ° C for 2 hours under argon protection to obtain Co-NC SACs material.

[0038] Step 3, dissolve 0.1g of ammonium molybdate tetrahydrate, 0.2g of thiourea and 0.12g of the Co-NC SACs material obtained in step 2 in 20mL of distilled water, stir, and transfer to a reactor after ultrasonic homogenization, and react at 200°C for 24h; after the reaction, wash and dry the obtained product, and then calcine at 700°C for 2h under argon protection to obtain the target product Co-NC@MoS2 SACs composite material.

[0039] Example 2

[0040] In this example, the Co-NC@MoS2 SACs composite material was prepared in the same manner as in Example 1, except that the mass of the cobalt nitrate hexahydrate in step 2 was 0.176 g.

[0041] Example 3

[0042] In this example, the Co-NC@MoS2 SACs composite material was prepared in the same manner as in Example 1, except that the mass of the Co-NC SACs material in step 3 was 0.24 g.

[0043] Comparative Example 1

[0044] In this comparative example, the Co-NC SACs material prepared in step 2 of Example 1 was used as a catalyst.

[0045] Comparative Example 2

[0046] This comparative example uses a separately prepared MoS2 nanomaterial as a catalyst, and its preparation steps are as follows:

[0047] Dissolve 0.1 g of ammonium molybdate tetrahydrate and 0.2 g of thiourea in 20 mL of distilled water, stir, and transfer to a reactor after ultrasonic homogenization. React at 200 °C for 24 h. After the reaction, wash and dry the product, and then calcine at 700 °C for 2 h under argon protection to obtain the target product, MoS2 material.

[0048] Figure 1 The X-ray diffraction patterns (XRD) of the catalyst materials prepared in Example 1 and Comparative Examples 1 and 2 are compared with the MoS2 (PDE#75-1539) standard card. The peaks at 14.1°, 39.5°, and 49.7° correspond to the three strong peaks on the card. It can be seen that the obtained materials successfully composited Co-NC SACs and MoS2.

[0049] Figure 2 This is the EDS energy spectrum of the Co-NC@MoS2 SACs composite material prepared in Example 1. It can be seen from the figure that the five elements C, N, Co, Mo and S in the composite material are evenly distributed.

[0050] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of the Co-NC@MoS2 SACs composite material prepared in Example 1. Figure 3 (a) and (b) show that the material is a nanosheet structure. Figure 3 (c) and (d) Observation of the lattice fringes in the selected area reveals the presence of few-layer pure 2H-MoS2 nanosheets with an enlarged interlayer spacing (0.632 nm).

[0051] Figure 4 The porous carbon nanosheet prepared in Example 1 ( Figure 4 (a)), Co-NC SACs ( Figure 4 (b)), MoS2 prepared in Comparative Example 2 ( Figure 4 (c)) and Co-NC@MoS2 SACs prepared in Example 1 ( Figure 4 Scanning electron microscope (SEM) image of (d)). Figure 4 (a) and (b) show that the porous carbon nanosheets and Co-NC SACs are both in the form of nanosheets. Figure 4 (c) It can be seen that MoS2 is in the shape of nanoflowers. Figure 4 (d) It can be seen that the Co-NC@MoS2 composite material is composed of lamellar MoS2 nanosheets uniformly coated on the outside of the Co-NC SACs material.

[0052] The materials prepared in the above embodiments are used as cathode catalyst materials for lithium-air batteries and assembled with lithium sheets into button-type lithium-air batteries. The assembly method is as follows: add a homogenate containing 60% KB, 30% catalyst material and 10% PVDF to the carbon paper collector. Then, dry it at 60°C in a vacuum drying oven for 12 hours. The net mass of the dried catalyst on the carbon paper is about 0.3-0.5 mg. Use lithium foil as the anode, lay a glass fiber separator flat, add 110 μL of electrolyte, add carbon paper with catalyst, and finally cover the cathode instrument with nickel foam as the filler, and complete the battery assembly in a glove box filled with argon. The test conditions are all carried out under pure oxygen conditions.

[0053] Figure 5 The first charge and discharge performance diagram of the lithium-air battery assembled with the catalyst materials prepared in Example 1 and Comparative Examples 1 and 2 shows that the lithium-air battery assembled with the Co-NC@MoS2 SACs composite material prepared in Example 1 has a high charge and discharge performance at 100mAg. carbon -1 At the constant current discharge density, the first discharge capacity reached 24896.46 mA hg carbon -1 The first discharge capacity of the lithium-air battery assembled with Co-NC SACs material in Comparative Example 1 was only 19898.17 mA hg carbon -1 The lithium-air battery assembled with MoS2 material in comparative example 2 only reached a specific capacity of 18218.5 mA hg in the first discharge. carbon -1 .

[0054] Figure 6The cycle performance diagram of the lithium-air battery assembled with the catalyst materials prepared in Example 1 and Comparative Examples 1 and 2 shows that the lithium-air battery assembled with the Co-NC@MoS2 SACs composite material prepared in Example 1 has a high cycle performance at 500 mA g carbon -1 At a constant current discharge density of , the capacity decayed after 210 cycles, showing good cycle stability. However, the capacity of the lithium-air battery assembled with Co-NC SACs material in comparative example 1 decayed after 130 cycles, and the capacity of the lithium-air battery assembled with MoS2 material in comparative example 2 decayed after 102 cycles.

[0055] Figure 7 The overvoltage diagram of the lithium-air battery assembled with the catalyst materials prepared in Example 1 and Comparative Examples 1 and 2 shows that the lithium-air battery assembled with the Co-NC@MoS2 SACs composite material prepared in Example 1 has a high overvoltage of 100 mA g carbon -1 At a constant current discharge density of , the overvoltage is about 1.01 V. The overvoltage of the lithium-air battery assembled with the Co-NC SACs material of Comparative Example 1 is 1.31 V, and the overvoltage of the lithium-air battery assembled with the MoS2 material of Comparative Example 2 is 1.05 V.

[0056] The test showed that the lithium-air battery assembled based on the Co-NC@MoS2 SACs composite material of Example 2 had a high current density of 500 mA g -1 At a constant current discharge density of 500 mA g, the capacity decayed after 88 cycles. -1 Under the constant current discharge density, the capacity decays after 135 cycles.

[0057] Figure 8 The ORR performance test diagram of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2, a to e represent the materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 respectively. The sample preparation and test method are as follows: 10 mg of catalyst, 2 mg of XC-72 and 40 μL of naphthol are dissolved in 2 mL of isopropanol aqueous solution (V 异丙醇 :V 水 =1:4), and after ultrasonication for 1h, a uniform mixed solution was obtained. 10μL of the solution was dropped on the glassy carbon electrode and air-dried for 2h to form a catalyst layer. LSV test was performed on the disk electrode. It can be seen from the figure that the catalyst prepared in Example 1 can reach the highest limiting current density during the test, and the catalytic effect is the best.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MoS2-coated porous MNC single-atom catalyst, characterized in that: First, the transition metal ions are chelated and anchored on the porous carbon support by a chelating agent, and then mixed with a nitrogen source precursor and calcined to obtain a material with porous nitrogen-doped carbon as a carrier and loaded with transition metal single atoms M, which is denoted as MNC SACs; then, through hydrothermal sulfurization and high-temperature calcination, the MNC SACs material is wrapped with layered MoS2 nanosheets to obtain a MoS2-coated porous MNC single-atom catalyst, which is denoted as MNC@MoS2SACs.

2. The method for preparing the MoS2-coated porous MNC single-atom catalyst according to claim 1, characterized in that: The steps include: Step 1, calcining 5-15 g of a carbon source precursor at 500-1000° C. for 1-10 hours to obtain a porous carbon nanosheet; Step 2, dissolving 1-5g of a chelating agent and 0.08-0.30g of a transition metal salt in deionized water and stirring evenly, then adding 0.05-0.2g of a porous carbon nanosheet and dispersing evenly by ultrasonication, standing for 12-24h, then centrifuging and drying, mixing and grinding the obtained powder with a nitrogen source precursor in a mass ratio of 1:2.5-10, and calcining at 500-1500°C for 1-10 hours to obtain MNC SACs; Step 3, 0.1-0.3g of molybdenum source, 0.2-0.4g of sulfur source and 0.1-0.2g of MNC SACs obtained in step 2 are evenly dispersed in 20mL of distilled water, transferred to a reactor, and reacted at 180-200°C for 15-36h; after the reaction, the obtained product is washed and dried, and then calcined at 500-1000°C for 2-4h to obtain the target product MNC@MoS2 SACs composite material.

3. The method for preparing the MoS2-coated porous MNC single-atom catalyst according to claim 2, characterized in that: The carbon source precursor is potassium phytate, anhydrous potassium citrate or plant fiber.

4. The method for preparing the MoS2-coated porous MNC single-atom catalyst according to claim 1 or 2, characterized in that: The chelating agent is glucose.

5. The method for preparing the MoS2-coated porous MNC single-atom catalyst according to claim 1 or 2, characterized in that: The transition metal is at least one of Fe, Co and Ni.

6. The method for preparing the MoS2-coated porous MNC single-atom catalyst according to claim 2, characterized in that: The transition metal salt is a nitrate, sulfate, acetate, oxalate or chloride of a transition metal.

7. The method for preparing the MoS2-coated porous MNC single-atom catalyst according to claim 2, characterized in that: The nitrogen source precursor is dicyandiamide, melamine or urea.

8. The method for preparing the MoS2-coated porous MNC single-atom catalyst according to claim 2, characterized in that: The sulfur source is thiourea, sulfur, mercaptan or thionine, and the molybdenum source is ammonium molybdate tetrahydrate, molybdenum trioxide, calcium molybdate or molybdenum hexafluoride.

9. A MNC@MoS2 SACs composite material prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the MNC@MoS2 SACs composite material according to claim 9, characterized in that: Used as positive electrode catalyst material for lithium-air batteries.

Citation Information

Patent Citations

  • Co-N / C@MoS2 composite material, preparation method and application in lithium air batteries

    CN110649271A

  • Porous carbon-loaded monatomic metal nitrogen coordination composite material and preparation method thereof

    CN111620311A

  • Preparation method and application of Cu / N doped carbon nanosheet catalyst with high stability

    CN111974435A

  • Doped transition metal monatomic catalyst as well as preparation method and application

    CN113258084A

  • Preparation method of bimetallic site monatomic catalyst and application of bimetallic site monatomic catalyst in electrocatalytic ammoxidation total denitrification reaction

    CN116550355A

Cited By

  • Secondary battery and preparation method thereof, energy storage system and electric equipment

    CN120089813A

  • Nitrogen-carbon anchored hollow structure catalyst and preparation method and application thereof

    CN121513933A

  • Nitrogen-doped carbon-loaded molybdenum-based monatomic catalyst as well as preparation method and application thereof

    CN121551044A